A proteção do consumidor contra as práticas comerciais abusivas no código de defesa do consumidor: novo ensaio para sistematização e aplicação do direito do consumidor - Wada, Ricardo Morishita (2017)
The present thesis aims to propose the systematization and application of the abusive commercial practices foreseen in the Consumer Protection Code, in the light of the post-positivist paradigm and the general lines of Friedrich Müller's Theory of Law. The discretionary and casuistic application provided by the positivist model does not allow to evaluate with clarity and transparency the values that constitute the decision, lessening both judicial and social control. In the proposed systematization, it is expected to remove the challenges of the current model and to ensure unity and order of the regimen of protection against abusive commercial practices, in order to strengthen its application and thus consumer protection. The abusive practices of the Consumer Protection Code were analyzed by through methodical normative program and the ambit of the norm. The national doctrine and the foreign experience have contributed to both the elaboration of the program of the norm and the interpretation of the linguistic elements. The scope of the norm was elaborated based on legal cases originated from the the Superior Court of Justice’s caselaw and from hypothetical cases related to the right of the consumer. The norm of protection against abusive practices has been fulfilled in many cases. In others, some questions were raised to be considered before the legal case